(untitled) (Research, Society and Development, 2020)
Microbiology is the science that studies microorganisms and their biological activities. Because they are microscopic organisms, it is a complex and abstract theme. Thus, the practical approach of this content is of paramount importance, with the use of various didactic methodologies. Thus, it is perceived that this subject requires a special look of the teachers. It is necessary to develop methodological strategies that encourage the critical sense of the student and stimulate learning. In view of this, this article aimed to present a systematic review of the literature on the use of different methodologies in the teaching of microbiology In order to identify research contributions related to this issue. The survey was carried out in the Google Scholar and Scielo databases. 8 relevant papers were selected. The results obtained showed the importance of using innovaite methodologies. Therefore, is stands out the need of the teacher adopt different methodologies in teaching of microbiology prioritizing an meaningful learning.